The Prolegomena To Christian Missiology - Soegianto Soegianto; Miduk Sampetua Sibagaring (Theological Journal Kerugma, 2022)
The title of this research article is The Prolegomena To Christian Missiology which discusses evangelism that must be carried out by Christians without exception, God's people are required not only to theorize but to carry out the commands that the Lord Jesus assigned to every believer. The purpose of writing this scientific article is to open up insight to the reader so that they have a broad determination and insight into the notion of evangelism. The conclusions from this study describe the following: first, faithful believers are disciples who are ready to plow and do not look back. Second, every believer must have ideas and actions in proclaiming the truth of God's Word. The Bible is a mission book from the Old Testament to the New Testament. The history of missions is the history of salvation in Christ Jesus the Messiah, the Son of God.